JOURNAL OF GOVERNMENT & POLITICS : A Comparative Analysis on the Strategy of Impression Management and Public Diplomacy of Two Indonesian Presidents At APEC CEO Summit - Inri Inggrit Indrayani (FISIPOL UMY, 2016)
This research aims to analyze speeches of the former Indonesian President Susilo Bambang Yudhoyono (SBY) and the current Indonesia President Joko Widodo (Jokowi) at the APEC CEO Summit.